RESPON PERTUMBUHAN RUMPUT GAJAH (Pennisetum purpureum var. Hawaii) YANG DIBERI PUPUK BOKASHI KOTORAN AYAM BROILER DENGAN DOSIS YANG BERBEDA - Asis Surajat; Natsir Sandiah; La Malesi (Universitas Halu Oleo, 2016)
This study aims to determine the best dose of fertilizer Bokashi broiler chicken manure on the growth of elephant grass. This study uses 64 trees planted elephant grass in a polybag, divided into 16 plots and the design of treatment used is Complete Random Design (RAL). This study consisted of 4 treatment that P0 (0 ton / ha Fertilizer Bokashi manure Broiler), P1 (10 ton / ha Fertilizer Bokashi manure Broiler), P2 (15 ton / ha Fertilizer Bokashi manure Broiler) and P3 (20 ton / ha Broiler Chicken manure Fertilizer Bokashi), and four replications. The research variables include plant height, number of tillers, stem diameter, number of leaves, number of segments, and root length. Analysis of data using analysis of variance followed by Duncan's multiple test. The results are: The average of plant height (cm / week / treatment) is (P0) 99.11, (P1) 132.45, (P2) 133.61, (P3) 129.95. The average number of saplings (tree / week / treatment) is (P0) 0.99, (P1) 1.46, (P2) 1.93, (P3) 2.3. Mean stem diameter (cm / Week / treatment) is (P0) 0.97, (P1) 1.44, (P2) 1.47 (P3) 1.37. The average number of leaves (Overlay / treatment) is (P0) 10.85, (P1) 19.89, (P2) 21.77, (P3) 22.56. The average number of segment (Segment / treatment) is (P0) 2.88, (P1) of 4.93, (P2) 4.38, (P3) 3.88. The average root length (cm / treatment) is (P0) 72.22 (P1) 98, (P2) 104.75 (P3) 98.75. Bokashi fertilizer application broiler chicken manure can increase the growth of elephant grass (Pennisetum purpureum var. Hawaii)with the best dose of 15 ton / ha. Keywords: Fertilizer Bokashi broiler chicken manure, gras